Instrumental and Technological Directions to Ensure Economic Security of Enterprise - Astakhov, Victor V.; Astakhova, Kateryna V.; Demin, Sergey S.; Sayadova, Julia B.; Mishchuk, Svetlana N.; Tkacheva, Natalia N. (International Review of Management and Marketing, 2016)
The market relations demands from heads of the enterprises not only implementation of process of production of goods (services), but also development of the program of management of economic security, as perspective direction of maintenance of technical and economic efficiency of a production activity of the enterprise. In the context of the analysis of economic security as efficiency parameter, the personnel safety coordinated to organizational culture of the enterprise gain special importance. Here comes to the forefront functions of the personnel responsible for carrying out this work at the enterprise, which is carrying out functions of observance of rules of economic security in interrelation with organizational culture of the enterprise. Weakening practically of any stage of financial and economic activity is reflected in complexity of economic security of the enterprise therefore management of the enterprise are in close interrelation with questions of economic security. Keywords: economic security, organizational culture, personalization JEL Classifications: D2; L84